FIBERGLASS CIRCULAR TURBULATOR IN COUNTER FLOW DOUBLE PIPE HEAT EXCHANGER: A STUDY OF HEAT TRANSFER RATE AND PRESSURE DROP - Sudiono Sudiono; Rita Sundari; Rini Anggraini (SINERGI, 2021)
This preliminary investigation studied the effect of circular turbulator vortex generator on heat transfer rate and pressure drop in a circular channel countercurrent double pipe heat exchanger with water working fluid. Increasing the number of circular turbulator yielded increasing heat transfer rate and pressure drop. The problem generated when increased pressure drop occurred in relation to more energy consumption of the water pumping system. Therefore, optimization in circular turbulator number is necessary to minimize the pressure drop about distance length between circular turbulator, tube diameter and thickness, type of material and crystal lattice, as well as the geometrical shape of fluid passage (circular or square). This study applied PVC outer tube and copper alloy inner tube, as well as fiberglass circular turbulator. The optimum results showed that seven parts of circular turbulator increasing heat transfer rate by 30% and pressure drop by 80% compared to that passage in the absence of circular turbulator at cool water debit of 7 L/min.